2018
DOI: 10.1080/02687038.2018.1463085
|View full text |Cite
|
Sign up to set email alerts
|

Use of co-verbal gestures during word-finding difficulty among Cantonese speakers with fluent aphasia and unimpaired controls

Abstract: Background Co-verbal gestures refer to hand or arm movements made during speaking. Spoken language and gestures have been shown to be tightly integrated in human communication. Aims The present study investigated whether co-verbal gesture use was associated with lexical retrieval in connected speech in unimpaired speakers and persons with aphasia (PWA). Methods & Procedures Narrative samples of 58 fluent PWA and 58 control speakers were extracted from Cantonese AphasiaBank. Based on the indicators of word-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 48 publications
2
8
0
Order By: Relevance
“…These findings are in line with those of Kroenke, Mueller, Friederici, and Obrig (2013). Other studies have similarly found that PWA gesture during instances of WFD but have not found evidence of facilitation (e.g., Cocks et al, 2011;Cocks, Dipper, Pritchard, & Morgan, 2013;Kong, Law, & Cheung, 2018;.…”
Section: Facilitative Gestures?supporting
confidence: 89%
See 1 more Smart Citation
“…These findings are in line with those of Kroenke, Mueller, Friederici, and Obrig (2013). Other studies have similarly found that PWA gesture during instances of WFD but have not found evidence of facilitation (e.g., Cocks et al, 2011;Cocks, Dipper, Pritchard, & Morgan, 2013;Kong, Law, & Cheung, 2018;.…”
Section: Facilitative Gestures?supporting
confidence: 89%
“…Taking the second question first, PWA did not differ from NHP in the overall number of gestures produced. Kong et al (2018) found a similar effect. However, there were clear differences in how those gestures related to speech.…”
Section: Discussionmentioning
confidence: 62%
“…The next step in the analysis was to separate coding categories into those describing form or function. Form categories were defined as those describing the physical properties of a gesture, while function categories described how the gestures were used in an utterance (Kong et al 2019). Table 1 illustrates how different gesture classifications were classed as form or function.…”
Section: Synthesis Of Coding Categoriesmentioning
confidence: 99%
“…2013, Kong et al . 2019). In interpreting these findings, we need to allow for the fact that not every gesture made by a person with aphasia is intended to aid lexical access.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation